Fracture Surface Investigations of Api Pipes Welded With Parameters Determined By Taguchi Method - Aşıkuzun, Elif; Çetinkaya, Cemil; Boz, Mustafa; Ada, Hakan (Sakarya University Journal of Science, 2018)
In this study, SEM images of the samples taken from welded nick break tests of API 5L X65 pipe joints, whose welding parameters were determined by Taguchi method, were examined. As a result of the investigations, the elongations and orientations exhibited by the grains showed that ductile and brittle fractures were observed in the welded joints. As it was observed from equiaxed, honeycomb like images that the fractures exhibited a ductile behavior. Brittle fractures that occurred due to cleavage breaks in some regions were detected. An  apparent effect of welding direction was observed in fracture behavior. It was detected from the SEM images that a ductile fracture structure had occurred in all joints that were performed from bottom to top, while it was observed in the joints performed from top to bottom that generally cleavage planes had developed along with fibrous structures in places, therefore brittle fractures had occurred.
Keywords: Chemistry; Engineering; API 5L X65; Fracture surface; SEM; Mühendislik; sem; api 5l x65; TA1-2040; Engineering (General). Civil engineering (General); QD1-999; fracture surface